Trends of Physics Critical Thinking Skill Research in Indonesia: A Systematic Literature Review - Santri Adi Putri; Nisa, Khairun; Kuswanto, Heru (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2024)
Critical thinking skills are fundamental in 21st-century teaching. This study aims to identify trends in research on critical thinking skills in physics in Indonesia, as reported in journal articles published between 2016 and 2022. This is meta-analysis research using the Prisma model. There were 36 articles that met the selection criteria. We performed the data analysis manually and used VOSviewer software. The indicators used for data analysis include the year, type of research, research subject, topic, treatment, data collection instrument, and the application of data analysis in each article. The analysis of article reviews reveals that the research trend for critical thinking skills in physics in Indonesia has increased, with more publications expected in 2020. Temperature and heat are the physics topics that have become the focus of research. High school students in grade X are the most frequently selected research subjects. Research on physics education typically employs quantitative methods, employs a quasi-experimental design, and utilizes a test as a data collection instrument. The most common method of data analysis in research is the t-test.